(untitled) (Research, Society and Development, 2022)
Introduction: In Brazil, according to data from SENAD 2009, 80% of college students reported drinking alcohol before age 18 and 49% used illicit drugs at some point in their lives, in a survey conducted in 100 college institutions. Another concern is the depression, a comorbidity that compromises the entire family and social life of the individual, predominating among young people. Objectives: To correlate the use of psychotropic substances with depression. Methodology: This is a cross-sectional study conducted on 137 physical therapy students from a university center in the interior of Minas Gerais, Brazil through the ASSIST questionnaire (Alcohol Smoking and Substance Involvement Screening Test) and the BDI-II questionnaire (Beck Inventory of Depression). Results: When correlating the studied variables, it was observed that the younger the age, longest the use of psychotropic drugs; its use is higher in females than in males; the use is higher in singles when compared to married or in consensual union; greater use in individuals living with parents compared to those living with spouses, spouses and children, other family members, boyfriends, alone, friends or republic, and there was no correlation between the use of opioids, alcohol, marijuana, tobacco, amphetamines, and hallucinogens and depression. Conclusion: Through the study, it can be observed that the use of psychotropic drugs in college students does not interfere with the development of depression, but further studies are necessary, as this issue may become a public health concern.